Mucinous cystic neoplasms of the liver: presence of biliary communication - Rodriguez, Robert M (J Surg Case Rep, 2019)
A 35-year-old woman was referred for a symptomatic liver mass. Diagnostic workup detected a septated cyst located centrally in the liver measuring 10 × 7 cm. The cyst had gradually increased in size from previous studies with new intrahepatic biliary dilation. Due to concern for malignancy and symptomatic presentation of the patient, a partial central hepatectomy was performed. Pathology revealed a smooth-walled, multiloculated cyst lined with mucinous epithelium and ovarian-type stroma. The diagnosis of low-grade mucinous cystic neoplasm of the liver (MCN-L) was made. Characteristics of MCN-L have not been elucidated due to its rarity.